Protein kinase A directly phosphorylates metabotropic glutamate receptor 5 to modulate its function. (4th March 2015) - Uematsu, Ken; Heiman, Myriam; Zelenina, Marina; Padovan, Júlio; Chait, Brian T.; Aperia, Anita; Nishi, Akinori; Greengard, Paul
Abstract Metabotropic glutamate receptor 5 (mGluR5) regulates excitatory post‐synaptic signaling in the central nervous system (CNS) and is implicated in various CNS disorders. Protein kinase A (PKA) signaling is known to play a critical role in neuropsychiatric disorders such as Parkinson's disease, schizophrenia, and addiction. Dopamine signaling is known to modulate the properties of mGluR5 in a cAMP‐ and PKA‐dependent manner, suggesting that mGluR5 may be a direct target for PKA. Our study identifies mGluR5 at Ser870 as a direct substrate for PKA phosphorylation and demonstrates that this phosphorylation plays a critical role in the PKA‐mediated modulation of mGluR5 functions such as extracellular signal‐regulated kinase phosphorylation and intracellular Ca2+ oscillations. The identification of the molecular mechanism by which PKA signaling modulates mGluR5‐mediated cellular responses contributes to the understanding of the interaction between dopaminergic and glutamatergic neuronal signaling.<boxed-text content-type="graphic" id="jnc13038-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> We identified serine residue 870 (S870) in metabotropic glutamate receptor 5 (mGluR5) as a direct substrate for protein kinase A (PKA). The phosphorylation of this site regulates the ability of mGluR5 to induce extracellular signal‐regulated kinase (ERK) phosphorylation and intracellular Ca2+ oscillations. This study provides a direct molecular mechanism by which PKA signaling interacts with glutamate neurotransmission.